Women's Prosocial Behavior in the Film Bolehkah Sekali Saja Kumenangis: A Social Psychology Study by Baron & Byrne - Anisa Anggun Septia; Anas Ahmadi (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the forms, motives, and roles of emotions as triggers for women's prosocial behavior in the film Bolehkah Sekali Saja Kumenangis. The study was conducted in 2025, using film scenes and dialogues containing prosocial actions as data sources. The population of this study comprised all scenes featuring female characters, while the sample comprised scenes that explicitly showed prosocial behaviour. Data were collected through a listening and note-taking technique using a prosocial behaviour coding sheet. Data analysis was carried out descriptively and qualitatively through an interactive analysis model that included data transcription, coding, classification, reduction, presentation, and concluding. The results showed that women's prosocial behaviour in the film comprises four main forms: empathy-altruism, the desire to reduce adverse circumstances, empathic pleasure, and genetic determinism. The prosocial motives of female characters are rooted in complex emotional experiences involving basic emotions such as sadness, anger, joy, fear, surprise, and disgust, which develop into compassion, guilt, and social concern. These results confirm that women's prosocial behavior is not only influenced by social norms, but also serves as a means of emotional recovery that strengthens empathy and social solidarity.